Global Analysis of Ecosystem Evapotranspiration Response to Precipitation Deficits. Issue 24 (28th December 2017) - He, Bin; Wang, Haiyan; Guo, Lanlan; Liu, Junjie
Abstract: Changes in ecosystem evapotranspiration (ET) due to precipitation deficits (PD) can relieve or aggravate soil moisture shortages, thus impacting drought severity. Previous findings have conflicted with regard to response of ET to PD. The present study relies on a global land ET synthesis data set (ETsyn ) and observations from eddy‐covariance towers (ETobs ) to thoroughly examine the sensitivity of ET to PD, which is represented by the standardized precipitation index. There was a contrast in the response to PD between arid and humid ecosystems. ETsyn of arid ecosystems was typically reduced promptly in response to a reduction of precipitation, while ETsyn in humid ecosystems experienced a two‐staged change: First, there was an enhancement, and then a reduction associated with persisting PD. Compared with ETsyn, ETobs suggests the occurrence of a more significant ET transition in response to PD. In arid ecosystems, ET typically negatively correlated with low PD, but this was limited by a large PD. Findings from this study are crucial for understanding the role of ET in drought evolution. Key Points: The relationship between ecosystem evapotranspiration and precipitation deficits was examined globally The sensitivity of ecosystem evapotranspiration to precipitation deficits revealed significant spatial heterogeneity Ecosystem evapotranspiration was observed to change in response to precipitation deficits in two stages